PENERTIBAN RENCANA TATA RUANG WILAYAH SEMPADAN SUNGAI CILIWUNG BERDASARKAN PERDA KABUPATEN BOGOR: Controlling Of Spatial Plans For The Ciliwung River Burier Area Based On Regional Regulation Of Bogor Regency - Ainina, Lia Qurrotu; Hasni, H (Faculty of Law, Universitas Trisakti, 2024)
Spatial planning is an effort to mitigate floods. The Regional Spatial Planning (RTRW) Plan of each district/city is stated in the Regional Regulations of each respective region. However, in its implementation, there are still violations committed by certain individuals, such as constructing buildings in river buffer zones. The issue raised is how the implementation of Regional Regulation No. 11 of 2016 concerning the Regional Spatial Planning of Bogor District 2016-2036 affects violations in the Upper Ciliwung River Buffer Zone, and the consequences of spatial violations in the said area. Thus, the first analysis reveals three samples of hotels/villas that have violated Article 71 letter a of the Bogor District Regional Regulation and have also violated zoning regulations and do not possess administrative permits. The second analysis involves the legal consequences for buildings in the Ciliwung